1.5 T magnetic resonance imaging generates accurate 3D proximal femoral models: Surgical planning implications for femoroacetabular impingement. Issue 9 (29th January 2020) - Malloy, Philip; Gasienica, Jacob; Dawe, Robert; Espinoza Orías, Alejandro A.; Nwachukwu, Benedict U.; Inoue, Nozomu; Yanke, Adam B.; Nho, Shane J.
Abstract: The objective of this study was to validate three‐dimensional (3D) proximal femoral surface models generated from a 1.5 T magnetic resonance imaging (MRI) by comparing these 3D models to those derived from the clinical "gold standard" of computed tomography (CT) scan and to ground‐truth surface models obtained by laser scans (LSs) of the excised femurs. Four intact bilateral cadaveric pelvis specimens underwent CT and MRI scans and 3D surface models were generated. Six femurs were extracted from these specimens, and the overlying soft tissues were removed. The extracted femurs were then laser scanned to produce a ground‐truth surface model. A 3D‐3D registration method was used to compare the signed and absolute surface‐to‐surface distances between the 3D models. Absolute agreement was evaluated using a 95% confidence interval (CI) derived from the precision of the LS ground‐truth. Paired samples t tests and Kolmogrov–Smirnov tests were performed to compare the differences between the signed and absolute surface‐to‐surface distances between the models. The average signed surface‐to‐surface distances for the MRI vs LS and MRI vs CT models were 0.07 and 0.16 mm, respectively. These differences fell within the 95% CI of ±0.20 mm indicating absolute agreement between the surface models generated from these modalities. The signed surface‐to‐surface distance was significantly smaller for MRI vs LS ground truth model as compared with the CT vs LS model. Femoral models derived from a 1.5 T MRI scan demonstrated absolute agreement with the clinical gold standard of CT‐derived models and were most like LS ground truth models of the excised femurs.